Web 2.0 – Based Agricultural Knowledge and Information Systems (AKIS 2.0) - Gyamfi, Albert (Journal of Strategic Innovation and Sustainability, 2020)
The study investigates how the media richness of web 2.0 technologies impact on their use for knowledge sharing among the primary knowledge actors in the Agricultural Knowledge and Information Systems as evidenced from the Cocoa Industry in Ghana. Three theories- Agricultural Knowledge and Information Systems (AKIS) model, SECI model, and the Media Richness Theory (MRT) were combined to establish that there exists a positive relationship between the tacitness of knowledge and media richness which can be used as the basis for selecting appropriate social media technologies for different types of the SECI processes for effective knowledge sharing